Citraan pada Kumpulan Puisi Bertema Musim Gugur Karya Goethe - Prahoro Yudo Purwono (Universitas Al Azhar Indonesia, 2021)
Imagery plays an important role in literary works, and poetry is no exception. In Goethe's poetry, the romantic era which tries to describe the beauty of nature as the main object is very strong. One of the natural beauties that are trying to be described and famous is autumn in Germany. This natural phenomenon is trying to be described through imagery, so readers need to understand the imagery in poetry to get a clear picture and understand the intent or message in the poem. This study aims to describe the meaning related to imagery and the types of imagery contained in Goethe's poems. The research method used is qualitative with the theory of Pradopo. The results showed that in the process of understanding the images or images contained in poetry, an understanding of the meaning contained in the poem as a whole was needed to get a clear picture. Meanwhile, based on the results of the analysis, found 4 types of imagery in Goethe's autumn-themed poetry, namely visual imagery, auditory imagery, tactile imagery, and motion imagery. The number of each image is 8 visual images, 2 auditory images, 2 tactile images, and 3 motion images.Keywords–Goethe, Imagery, Poetry, Herbsgedichte